Wandi's Little Voice - Banda-Aaku, Ellen (Book collections on Project MUSE., 2021)
Wandi's Little Voice is a story set in a Lusaka suburb. It is about a young girl transitioning into adolescence. It was first published in 2004 by Macmillan Education in South Africa and won the Macmillan Writers Prize for Africa.